Pengaruh Social Media Marketing, Inovasi Produk, dan Persepsi Harga Terhadap Minat Beli Pada Smartphone Xiaomi Seri Redmi: (Studi Kasus Mahasiswa Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Bhayangkara Jakarta Raya) - Jeremy Steven; Neng Siti Komariah; Haryudi Anas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research was conducted to determine the partial or simultaneous influence of the independent variables, namely Social Media Marketing, Product Innovation, and Price Perception on the dependent variable, namely Purchase Interest. This research uses quantitative methods. The population in this study were students of the Management Study Program, Faculty of Economics and Business, Bhayangkara University, Jakarta Raya. Determining the sample size for this study used the purposive sampling method with the Slovin formula with a sample size of 100 respondents. Based on the research results, it is known that: 1) The results of this research show that the Social Media Marketing variable influences the interest in purchasing Xiaomi Redmi series smartphones. 2) The results of this study show that the Product Innovation Variable has no effect on Purchase Interest in the Xiaomi Redmi series Smartphone. 3) The results of this research show that the Price Perception Variable influences Intention to Buy Xiaomi Redmi Series Smartphones. 4) The results of this research show that the variables Social Media Marketing, Product Innovation, and Price Perception have an influence on Purchase Interest in the Xiaomi Redmi series Smartphone.